2010
DOI: 10.1063/1.3323092
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscope study of striated carbon ridges in few-layer epitaxial graphene formed on 4H-silicon carbide (0001¯)

Abstract: Atomically resolved scanning tunneling microscope images of carbon ridge defects found in few-layer graphene formed on the C-face (0001¯) of 4H-silicon carbide reveal a striated exterior surface formed from out-of-plane distortions of the hexagonal graphene lattice. While ridge formation is likely explained by compressive in-plane stresses coupled with the small values of the bending modulus for few-layer graphene, the striated structure along the ridges argues for a localized unidirectional stress in the mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…6,28,29 In epitaxial few-layer graphene grown on SiC, a distinct ridgelike network of defects formed from the out-of-plane distortions of the hexagonal graphene lattice was observed, which results in the formation of Moiré patterns clearly seen in atomically resolved scanning tunneling microscopy images. 28,29 For natural graphite, the surface is usually inhomogeneous and presents a variety of defects as well. By low-temperature STS experiments, in the region separated by a macroscopic ridgelike defect, single-layer graphene flakes decoupled from the surface of highly oriented pyrolitic graphite have been found.…”
Section: Resultsmentioning
confidence: 99%
“…6,28,29 In epitaxial few-layer graphene grown on SiC, a distinct ridgelike network of defects formed from the out-of-plane distortions of the hexagonal graphene lattice was observed, which results in the formation of Moiré patterns clearly seen in atomically resolved scanning tunneling microscopy images. 28,29 For natural graphite, the surface is usually inhomogeneous and presents a variety of defects as well. By low-temperature STS experiments, in the region separated by a macroscopic ridgelike defect, single-layer graphene flakes decoupled from the surface of highly oriented pyrolitic graphite have been found.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main growth issues to be prevented is morphological ununiformity as typified by a ridge structure, which is commonly observed at the surface of multilayer graphene on C-face of hexagonal SiC. This unfavorable structure is considered as a result of thermal stress at the topmost graphene layer(s), which is less interactive with its underlying SiC interface [6]. Therefore, it is important to study the ridge formation dynamics associated with growth temperatures in wider range.…”
Section: Introductionmentioning
confidence: 99%
“…Ripples are also observed in various literatures [32,33]. with their experimental observations [34]. Since imperfect graphene sheets will strongly influence their properties, various attempts have been made to understand the cause of these intrinsic ripples.…”
Section: Intrinsic Imperfectionsmentioning
confidence: 79%
“…Shenoy addressed the issue based on elastic plate theory and suggested that it is the compressive edge-stress along both the armchair and zigzag edges that lead to the warping of graphene sheets [37]. In addition to thermal effects and intrinsic stress, Harrison concluded that the localized unidirectional stress along the ridge length may result in the striated structure observed around ridges [34]. Other imperfections of graphene sheets, such as single vacancy and Stone-Wa les defects, alter their chemical, electronic [38], and mechanical properties [39,40].…”
Section: Intrinsic Imperfectionsmentioning
confidence: 99%